2018
DOI: 10.1101/495564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of young and old adult brains: An EEG functional connectivity analysis

Abstract: Brain connectivity studies have reported that functional networks change with older age. We aim to (1) investigate whether electroencephalography (EEG) data can be used to distinguish between individual functional networks of young and old adults; and (2) identify the functional connections that contribute to this classification. Two eyes-open resting-state EEG recording sessions with 64 electrodes for each of 22 younger adults (19-37 years) and 22 older adults (63-85 years) were conducted. For each session, i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…There has been significant interest in studying task-based or resting-state brain's functional connectivity in healthy and patient subjects, which has resulted in new understanding about the brain function as well as the mechanisms underlying brainrelated disorders [117,118,119,120,121,122,123,124,125,17,126]. In BCIs, functional connectivity measures have been employed as features to discriminate various tasks [28,26,27,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant interest in studying task-based or resting-state brain's functional connectivity in healthy and patient subjects, which has resulted in new understanding about the brain function as well as the mechanisms underlying brainrelated disorders [117,118,119,120,121,122,123,124,125,17,126]. In BCIs, functional connectivity measures have been employed as features to discriminate various tasks [28,26,27,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported changes in FC in different frequency bands with cognitive tasks, aging and with brain disorders (Ishii et al, 2017). For example, reduction in alpha (8-12 Hz) FC was reported with healthy aging in resting state EEG (Moezzi et al, 2019), while gamma (30-55 Hz) FC reduction was reported in autism (Safar et al, 2020), and in Alzheimer's Disease (AD) and schizophrenia (Uhlhaas and Singer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Long-range synchrony between frontal and parietal cortices in the Beta band has been observed to dominate during top-down attentional processing (Buschman and Miller, 2007) and is thought to support the enhancement of task-relevant information (Antzoulatos and Miller, 2016). There is also some evidence that Beta band connectivity increases with aging (Moezzi et al, 2019; Vysata et al, 2014). The results did not yield support for previous observations of inter-hemispheric asymmetry reduction with age (Dolcos et al, 2002) in terms of increasing inter-hemispheric connectivity (Maurits et al, 2006).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%